2018
DOI: 10.1038/s41390-018-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous premature birth as a target of genomic research

Abstract: Spontaneous preterm birth is a serious and common pregnancy complication associated with hormonal dysregulation, infection, inflammation, immunity, rupture of fetal membranes, stress, bleeding, and uterine distention. Heredity is 25-40% and mostly involves the maternal genome, with contribution of the fetal genome. Significant discoveries of candidate genes by genome-wide studies and confirmation in independent replicate populations serve as signposts for further research. The main task is to define the candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 94 publications
0
18
0
1
Order By: Relevance
“…Thus, varying pathways leading to SPTB could partly explain the variations in the results among the datasets. Maternal, and also to some extent fetal, genomes affect the susceptibility to preterm birth and duration of pregnancy in general 23 , 47 , 48 . We analyzed several maternal and fetal GWAS and WES datasets to identify HSP and NR genes associated with preterm birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, varying pathways leading to SPTB could partly explain the variations in the results among the datasets. Maternal, and also to some extent fetal, genomes affect the susceptibility to preterm birth and duration of pregnancy in general 23 , 47 , 48 . We analyzed several maternal and fetal GWAS and WES datasets to identify HSP and NR genes associated with preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…We used multiple available sources of preterm birth GWAS data, including both maternal and fetal genomes. The first dataset we used comprised 43,568 mothers of European ancestry; these mothers were identified from among 23andMe’s research participants as described previously 48 . The second dataset included meta-analysis data for 4632 mothers and their 1960 infants from three independent Nordic (Finnish, Danish, and Norwegian) preterm birth case/control data sets of European ancestry 31 .…”
Section: Methodsmentioning
confidence: 99%
“…We expect that our model will facilitate mechanistic studies of reproductive-disease-related genes as identified by animal models and, importantly, human genome-wide association studies (GWASs) and gene regulatory mapping studies (Hallman et al, 2019;Zondervan et al, 2016;Sakabe et al, 2020). For example, recent studies have reported that a novel causal locus and candidate gene, HAND2, is associated with gestational length (Sakabe et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The recent increase in environmental pollution, which is associated with high PM concentrations, has been shown to have negative effects on maternal immunity and neonatal health [11]. PM exposure may induce reproductive toxicity mediated by placental DNA methylation and maternal inflammatory responses, suggesting a link between PM exposure and preterm birth risk [12].…”
Section: Introductionmentioning
confidence: 99%